Spanish parents' emotion talk and their children's understanding of emotion - Aznar, Ana; Tenenbaum, Harriet R. (Frontiers in Psychology, 2013)
Relations between parent-child emotion talk and children’s emotion understanding were examined in 63 Spanish mothers and fathers and their 4- (M = 53.35 months, SD = 3.86) and 6-year-old (M = 76.62 months, SD = 3.91) children. Parent-child emotion talk was analyzed during two storytelling tasks: a play-related storytelling task and a reminiscence task (conversation about past experiences). Children’s emotion understanding was assessed twice through a standardized test of emotion comprehension (TEC; Pons, Harris, & de Rosnay, 2004), once before one of the two parent-child storytelling sessions and again six months later. Mothers’ use of emotion labels during the play-related storytelling task predicted children’s emotion understanding after controlling for children’s previous emotion understanding. Whereas fathers’ use of emotion labels during the play-related storytelling task was correlated with children’s emotion understanding, it did not predict children’s emotion understanding after controlling for previous emotion understanding. Implications of these findings for future research on children’s socioemotional development are discussed.